Language restandardization in Croatia: Problems and Perspectives - Peti-Stantić, Anita (Array, 2008)
In this paper the authors treat language policies in Croatia in the period since 1991 as an example of restandardization, within a theoretical framework which takes into account the intersecting roles of national(ist) ideologiy, rhetoric and language myths in contemporary Croatian society. The analysis is based on published sources and data from text corpora and two surveys of language attitudes among teachers. The term "restandardizatio", in contrast to other possible labels such as "corpus planning" or "language reform", presupposes the existence of a standardized Croatian language prior to the period in question.